CULTURAL AND EDUCATIONAL WORK IN THE TOWNS OF DAGHESTAN IN THE 20S - 90S OF THE 20TH CENTURY - Mirzabekov, Mirzabek Ah'aevic (History, Archeology and Ethnography of the Caucasus, 2018)
The paper is devoted to the history and problems of cultural and educational work in the Daghestan towns in the 20s - 90s of the 20th century. Using a wide range of archival materials, statistical data, works of Daghestan historians, for the first time in regional historiography a wide panorama of cultural and educational work in towns of the republic has been recreated for a large chronological period of time. The work shows the increase of the network, strengthening of the scope of cultural and educational work in the Daghestan town. There was a rejection and opposition to it from a certain religiously minded part of the urban population of the region. The origin of new forms and types of work in the activities of cultural and educational institutions has been traced. It is noted that by the end of the second decade of Soviet power, they have become an important component of the social and cultural life of the Daghestan town. The work shows the contribution of urban cultural and educational institutions in mobilizing the spiritual and moral potential of Daghestanis during the Great Patriotic War to repulse the enemy and achieve a sooner Victory, and the help in this socially important activity of the theaters evacuated to the region. Much attention is paid to the coverage of problems of cultural and educational work in towns of the republic in the post-war decades. Based on reliable factual material, the author, despite the remaining difficulties and unsolved problems, traces the increase in the scope and quality of ongoing cultural events in the cities of the region during this period. The paper also reflects the assistance of the federal center in the development of cultural and educational work in the republic.